Synthesis of SPIO Nanoparticles and the Subsequent Applications in Stem Cell Labeling for Parkinson’s Disease - Li An; Qing Tao; Yue Wu; Nana Wang; Yan Liu; Feifei Wang; Lixing Zhang; Aihua Shi; Xiumin Zhou; Shuang Yu; Jingzhong Zhang (Nanoscale Research Letters, 2021)
Abstract Parkinson's disease (PD) is characterized by the progressive loss of dopaminergic neurons in the midbrain, and the stem cell transplantation method provides a promising strategy for the treatment. In these studies, tracking the biological behaviors of the transplanted cells in vivo is essential for a basic understanding of stem cell function and evaluation of clinical effectiveness. In the present study, we developed a novel ultrasmall superparamagnetic iron oxide nanoparticles coating with the polyacrylic acid (PAA) and methoxypolyethylene glycol amine (PEG) by thermal decomposition method and a two-step modification. The USPIO-PAA/PEG NPs have a uniform diameter of 10.07 ± 0.55 nm and proper absorption peak of the corresponding ligands, as showed by TEM and FTIR. MTT showed that the survival of cells incubated with USPIO-PAA/PEG NPs remained above 96%. The synthesized USPIO-PAA/PEG had a good relaxation rate of 84.65 s−1 Mm−1, indicating that they could be efficiently uptake and traced by MRI. Furthermore, the primary human adipose-derived stem cells (HADSCs) were characterized, labeled with USPIO-PAA/PEG and transplanted into the striatum of 6-hydroxydopamine (6-OHDA)-induced PD rat models. The labeled cells could be traced by MRI for up to 3 weeks after the transplantation surgery; moreover, transplantation with the labeled HADSCs significantly attenuated apomorphine-induced rotations in PD models and increased the number of the dopaminergic neurons in the substania nigra. Overall, the development of USPIO-PAA/PEG NPs provides a promising tool for in vivo tracing technique of cell therapy and identifies a novel strategy to track stem cells with therapeutic potential in PD.